2014
DOI: 10.1371/journal.pone.0093468
|View full text |Cite
|
Sign up to set email alerts
|

Automated Analyses of Innate Olfactory Behaviors in Rodents

Abstract: Olfaction based behavioral experiments are important for the investigation of sensory coding, perception, decision making and memory formation. The predominant experimental paradigms employ forced choice operant assays, which require associative learning and reinforced training. Animal performance in these assays not only reflects odor perception but also the confidence in decision making and memory. In this study, we describe a versatile and automated setup, “Poking-Registered Olfactory Behavior Evaluation Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…Odor preference is often assessed using place preference by associating odors with their spatial locations. However, intrinsic bias in spatial preference and scent marking can confound the readout 12,13 . To avoid intrinsic place bias, we have devised a computerized setup, PROBES, to perform automated single-chamber odor preference assays 12 .…”
Section: Odor Mixing Abolishes Innate Valencementioning
confidence: 99%
See 3 more Smart Citations
“…Odor preference is often assessed using place preference by associating odors with their spatial locations. However, intrinsic bias in spatial preference and scent marking can confound the readout 12,13 . To avoid intrinsic place bias, we have devised a computerized setup, PROBES, to perform automated single-chamber odor preference assays 12 .…”
Section: Odor Mixing Abolishes Innate Valencementioning
confidence: 99%
“…However, intrinsic bias in spatial preference and scent marking can confound the readout 12,13 . To avoid intrinsic place bias, we have devised a computerized setup, PROBES, to perform automated single-chamber odor preference assays 12 . This setup provides an efficient and robust readout of the sampling of a single odor port in the habituation/dishabituation test ( Fig.…”
Section: Odor Mixing Abolishes Innate Valencementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that rodents are very good at olfactory discrimination, memory, and decision (Abraham et al, 2004, Barnes et al, 2008, Cleland et al, 2002, Haddad et al, 2013, Hubener and Laska, 2001, Kepecs et al, 2007, Komiyama et al, 2010; Liu et al, 2014, Lu et al, 1993, Mihalick et al, 2000, Passe and Walker, 1985, Petrulis and Eichenbaum, 2003, Rinberg et al, 2006, Slotnick et al, 1991, Uchida and Mainen, 2003). Automatic behavioral systems have been developed for studying innate olfactory behaviors (Qiu et al, 2014). Olfactory behavioral testing has been developed in head-fixed rodents and greatly facilitates the understanding of neural circuits underlying olfaction (Verhagen et al, 2007; Wesson et al, 2008; Shusterman et al, 2011; Kato et al, 2013; Boyd et al, 2015) and odor-based cognition (Komiyama et al, 2010; Liu et al, 2014; Gadziola et al, 2015).…”
Section: Introductionmentioning
confidence: 99%